The Effectiveness of Learning Strategy based on "SETARA DARING" Application at Equivalency Education in Community Learning Center in Jakarta - Ahmad Suryadi; Ansharullah Ansharullah; Lilik Subaryanto; Zainal Arif (AL-ISHLAH: Jurnal Pendidikan, 2023)
The equivalency education programme (EEP) gives people who failed basic and secondary school a second chance. “Paket A” represents primary education (SD), “Paket B” junior secondary (SMP), and “Paket C” senior secondary (SMA) in EEP. In 2017, the Ministry of Education and Culture created "SETARA DARING" to boost EPP learning. The purpose of this research is to examine the effectiveness of online-based learning strategies through the application of SETARA DARING on equality education organized by the Community Learning Center (PKBM) in DKI Jakarta. The research method uses the CIPP (Context, Input, Process, Product) technique developed by Stufflebeam. PKBM, which practices SETARA DARING in DKI Jakarta, hosted the research. This study found the following. The context evaluation found that SETARA DARING met ICT-based and online learning challenges. Many equity education students are older and working. The input evaluation of SETARA DARING's application included prepared components and distance learning. The Ministry of Education and Culture provides sufficient resources, facilities, and funds for SETARA DARING. In process evaluation, the SETARA DARING application is still not working successfully since the non-formal education programme has not gotten support, technical direction, capacity building, facilities and equipment assistance, or data access. Product evaluation shows that SETARA DARING application development and use have not met expectations. The Directorate General of Early Childhood Education and Community Education cannot support SETARA DARING. Developing and using SETARA DARING requires technical assistance and capacity building for infrastructure and human resources, as well as financial support for equality education providers in PKBM, SKB, and homeschooling. Thus, the Directorate of Education and Special Education must execute and build the SETARA DARING application, which has a noble objective to provide alternative education services through non-formal education in PKBM, especially in Jakarta.